Usefulness of follicular fluid estradiol and progesterone concentration measurement in predicting outcome of IVF/ICSI natural cycles. - Vida Gavrić Lovrec; Veljko Vlaisavljević; Borut Kovačič; Maksimiljan Gorenjak; Milan Reljič (Acta Medico-Biotechnica, 2021)
Purpose: The aim of the study was to establish whether follicular fluid (FF) estradiol (E2) and progesterone (P) measurement could be used to predict the outcome of unstimulated IVF/ICSI cycles.Methods: 91 women underwent 150 unstimulated IVF/ICSI cycles (78 IVF and 72 ICSI). Follicular fluid samples were collected at the time of oocyte recovery. Using the ttest, FF E2 and FF P levels and their ratios (FF P/FF E2) were compared between cycles with successful (with oocyte) and unsuccessful (without oocyte) oocyte recovery, between cycles with and without fertilization and between nonconception and conception cycles.Results: The oocyte recovery rate was 86.7% (123/150), the fertilization rate 68.3% (84/123) and the pregnancy rate per oocyte recovery 14.0% (21/150). The average FF E2 level was 3530 ± 1339 nmol/L, average FF P 20649 ± 9489 nmol/L and average FF P/FF E2 ratio 7.18 ± 6.42. There were no statistically significant differences in FF E2, FF P levels and their ratio between cycles with unsuccessful and successful oocyte recovery, between cycles without and with fertilization, and between nonconception and conception cycles.Conclusion: From the FF E2 and P levels and their ratio, it is not possible to make inferences to the likelihood of oocyte recovery, fertilization and conception in unstimulated IVF/ICSI cycles.